FUNGSI BAHASA DALAM RUANG DIGITAL: ANALISIS SOSIOPRAGMATIK PADA PLATFROM TIKTOK - Wahyuni, Andi Ruhul; Saleh, Muhammad (Manifestasi: Jurnal Pendidikan dan Pengajaran, 2025)
This study aims to analyze the functions of language in digital spaces by examining communication patterns among TikTok users from a sociopragmatic perspective. As a short-video platform, TikTok presents unique interaction characteristics, including informal language, code-mixing, humor, and distinct politeness strategies compared to face-to-face communication. Using a qualitative content analysis approach, this research investigates comments, captions, and other interactive features in viral videos. The findings reveal that language on TikTok functions not only as a communication tool but also as a medium for shaping identity, social intimacy, cultural resistance, and meaning negotiation. These phenomena show that digital language dynamics reflect broader social and cultural changes in contemporary society